A study on prevalence and determinants of postpartum depression among mothers: a cross-sectional study - H., Nisarga; Preethimol; Siddiq, Abubaker (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Postpartum depression (PPD) is a common affective disorder. It remains unrecognized and affects the health of mothers and the interpersonal relationships, mother infant bonding as well as emotional and cognitive behavior of baby. It occurs immediately or 2 to 6 weeks after delivery and may last for a year. This study aims at determining the prevalence of PPD among mothers, its associated factors and to correlate mothers age and parity in PPD. Method: It is a cross sectional study conducted in department of obstetrics and gynecology (OBG) in a tertiary care hospital. we have enrolled one seventy-two (172) postpartum women within six months of their delivery after obtaining informed consent. Edinburgh postnatal depression scale was used for determining the prevalence. Sociodemographic and obstetrics questionnaire were given to identify associated factors and correlation between mothers age and parity. Results: Out of 172 enrolled patients, we collected information about PPD, in our study the prevalence of PPD was 44%. Age, marital status, education of mother, occupation of mother, Occupation of husband, wealth index, social support by family, husband substance abuse, type of family, gender of baby, parity, mode of delivery, present pregnancy, sex preference of mother, infant illness, are the factors associated with PPD. Age and parity have no correlation with PPD. Conclusions: The high prevalence rate of PPD and associated risk factors imply the need for strengthening and improving of postpartum care.